OPTIMALISASI PEMANFAATAN PEKARANGAN - M. Alhudhori (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The purpose of this study is to conduct optimization of utilization of food sufficiency Grounds to support rural families in the Western Cape District Jabung, so as to enhance the fulfillment of family food. The research method used was survey method, a research by taking a sample from a population which aims at obtaining a generalization insofar as the population from which the sample was taken, as for the phase of research is mitigation activities, data collection, focused group discussion. The conclusions of this study, namely the optimization utilization of yard can be done by developing sustainable food home with the right technique, namely through the creation of groups, the identification of needs, the preparation of a plan of activities, training event, the creation of nurseries and structuring the environment of the area.Proper development techniques able to embody the replication area homes preserved food quickly and can provide real benefits for your family and the environment.Keywords : Yard, The Home Of Sustainable Food